Effect of Dietary Supplementation with Sources of Omega-3 and Omega-6 Fatty Acids on Certain Blood Characteristics of Laying Quail - Al-Daraji, Hazim J.; Al-Hassani, Ali S.; Al-Mashadani, H.A.; Al-Hayani, W.K.; Mirza, H.A. (International Journal of Poultry Science, 2010)
The objective of this experiment was to determine the effects of dietary supplementation with different fat sources on blood parameters of Japanese quail (Coturnix coturnix japonica). Eighty four 7-week old laying quail were randomly assigned to 4 treatment groups (21 birds per group) with 3 replicates for each treatment group and fed for three months on a commercial diet supplemented with 3% of either sunflower oil (T1), flax oil (T2), corn oil (T3) or fish oil (T4). The birds received water and feed ad libitum during the experiment. During the last month of experiment blood samples were collected fortnightly from each bird. The first blood samples collection was used to determine fresh blood parameters, while the second blood samples collection was used after pooled blood samples for each replicate of treatment group to determine serum chemistry traits. Dietary supplementation with 3% fish oil (T4) caused a significant (p<0.05) increase in erythrocyte number, Packed Cell Volume (PCV), hemoglobin concentration, Mean Corpuscular Values (MCV), Mean Corpuscular Hemoglobin (MCH), Mean Corpuscular Hemoglobin Concentration (MCHC), thrombocyte number and leukocyte number and serum total protein, albumen, globulin, glucose, High Density Lipoprotein (HDL), Alkaline Phosphatase (ALP), calcium and phosphorus concentration, followed by the results of flax oil (T2), whereas sunflower oil (T1) and corn oil (T3) revealed the lowest values respecting these traits. However, adding sunflower (T1) and corn oil (T3) to the diet of laying quail resulted in significant (p<0.05) increase in percentage of reticulocytes and Heterophil to Lymphocyte (H/L) ratio and serum total cholesterol, triglycerides, Low Density Lipoprotein (LDL), uric acid, creatinine, Aspartate Aminotransferase (AST) and alanine aminotransferase (ALT), followed by the results of the flax oil (T2), while fish oil (T4) exhibited the lowest means with relation to these traits. From this experiment it is concluded that dietary fish and flax oils at inclusion level of 3% resulted in significant improvement in blood profile of laying quail. Consequently, fish and flax oils can be added during the laying period to the diet of Japanese quail to enhance general physiological status of these birds.